Síntese, caracterização e aplicação de dióxido de titânio em células fotovoltaicas - Paula, Fernando Rogério [UNESP] (My University, 2018)
Research in photovoltaic cells is highly current and of great importance, as there is a moment of transition between the use of fossil energy resources and renewable energy sources. However, despite the growth in the use of photovoltaic cells as a source of renewable electrical energy, the expansion of its use in a more intensive way comes up against the cost of production. This cost, however, has been decreasing rapidly in recent years, mainly due to research into new active materials for photovoltaic cells. Currently, the rapid and recent expansion of organic materials as active elements in photovoltaic cells places conjugated conductive polymers among the most promising materials. This work developed hybrid organic/inorganic photovoltaic cells using P3HT as the active layer and TiO2 as an acceptor of photogenerated electrons. The results obtained with confocal microscopy on TiO2/P3HT films showed that the TiO2 film effectively acts as an electron acceptor in the exciton dissociation process. This behavior was confirmed by measuring the efficiency of photovoltaic cells. The TiO2 film obtained with the electrodeposition potential of 1.00 V showed the highest efficiency, around 0.76%.

A pesquisa em células fotovoltaicas é extremamente atual e de grande importância, pois se vive um momento de transição entre a utilização de recursos energéticos fósseis e de fontes energéticas renováveis. Contudo, apesar do crescimento da utilização de células fotovoltaicas como fonte geradora de energia elétrica renovável, a expansão do uso da mesma de forma mais intensiva esbarra no custo de produção. Este custo, entretanto, vem baixando rapidamente nos últimos anos devido principalmente às pesquisas em novos materiais ativos de células fotovoltaicas. Atualmente a rápida e recente expansão do uso de materiais orgânicos como elementos ativos em células fotovoltaicos colocam os polímeros condutores conjugados entre os materiais mais promissores. Dentro deste contexto, neste trabalho, foram desenvolvidas células fotovoltaicas híbridas orgânicas/inorgânicas utilizando o P3HT como camada ativa e o TiO2 como aceptor de elétrons fotogerados. Os resultados obtidos com a microscopia confocal em filmes de TiO2/P3HT mostraram que o filme de TiO2 atua efetivamente como aceptor de elétrons no processo de dissociação do éxciton. Este comportamento foi confirmado pela medida da eficiência das células fotovoltaicas. O filme de TiO2 obtido com o potencial de eletrodeposição de 1,00 V foi o que apresentou a maior eficiência, entorno de 0,76 %.
Synthesis, characterization, and application of titanium dioxide in photovoltaic cells
Keywords: Photovoltaic cells; Titanium dioxide; Renewable energy; Conducting polymers; Células fotovoltaicas; Dióxido de titânio; Energia renovável; Polímeros condutores